Fracture nonunion and delayed union - David S. Liu, MD; Brian D. Snyder, MD, PhD; Susan T. Mahan, MD, MPH (Elsevier, 2024)
ABSTRACT: Delayed union and nonunion of fractures exist in the pediatric population. Fracture healing requires the synergistic collaboration of mechanical support and robust biological processes to allow endochondral ossification, reestablishment of bone continuity, and subsequent remodeling to strong lamellar bone. Failure of either mechanical stability or biology may manifest as delayed fracture healing. While early recognition of potential metabolic and pharmacologic risk factors may be addressed by pre-emptive treatment using nutritional and vitamin D supplements, definitive treatment of established nonunion requires a comprehensive approach. Key Concepts: (1) Delayed unions and nonunions are more common in adult bone but can also occur in pediatric bone. (2) Fracture healing requires synergistic collaboration of mechanical support and robust biological processes; treatment of nonunions should address both the biological and mechanical factors. (3) Vitamin D is an integral component of calcium absorption and bone health.